2020
DOI: 10.1080/02643944.2020.1713868
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and pupils under pressure: UK teachers’ views on the content and format of personal, social, health and economic education

Abstract: Statement of contribution: ELD conceived the idea for the paper and designed the survey. FM collected and analysed the data. ELD drafted initial versions of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…However, as PSHE resources suggest that harm reduction should be taught if the curriculum resources are followed, as well as skill-based and affective intervention elements (Faggiano et al , 2008), it is likely that the issue lies in the implementation of the prevention education, which echoes findings from Stead et al (2010) and Waller et al (2017). Davies and Matley (2020), Stead et al (2010) and Waller et al (2017) all highlight lack of teacher training and inappropriate or lack of resources as negatively influencing implementation of prevention education. The PSHE Association (2015) attribute this in part to the non-statutory status of PSHE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as PSHE resources suggest that harm reduction should be taught if the curriculum resources are followed, as well as skill-based and affective intervention elements (Faggiano et al , 2008), it is likely that the issue lies in the implementation of the prevention education, which echoes findings from Stead et al (2010) and Waller et al (2017). Davies and Matley (2020), Stead et al (2010) and Waller et al (2017) all highlight lack of teacher training and inappropriate or lack of resources as negatively influencing implementation of prevention education. The PSHE Association (2015) attribute this in part to the non-statutory status of PSHE.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the PSHE Association (2015) argue that it has not been held to the same rigorous standards as other subjects. With no central curriculum for PSHE education, the drug education young people receive varies greatly between schools (Davies and Matley, 2020; PSHE Association, 2016). Similarly, several systematic reviews highlight a number of different approaches to drug prevention education (Agabio et al , 2015; Demant and Schierff, 2019; Faggiano et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Rouse and Hadley [29] identified that staff only evaluate themselves according to the children's academic performance, failing to account for the love and caring that they provide at the practical level. Scholars have also pointed out that burnout, high-stress levels, and turnover are general issues facing ECEC [30] and the numbers of staff affected by these issues have increased recently within the UK [31,32]. At the same time, the inclusion of all children means staff must adapt their pedagogy, content, and methods to the needs of each individual student, making it an essential part of the staff's working agenda [17].…”
Section: Introductionmentioning
confidence: 99%